Estudo farmacológico dos efeitos gastrointestinais e comportamentais do lupeol e da dilactona do ácido valonéico, isolados de Cenostigma macrophyllum Tul., em roedores - Lira, Silveria Regina de Sousa (2010)
The Lupeol triterpene and valoneic acid dilactone (VAD), two major chemical components isolated from Cenostigma macrophyllum Tul. (Leguminoseae) were evaluated in the experimental model gastric lesion induced by ethanol and in animal models of behavioral. Both lupeol (3, 10 and 30 mg/kg, p.o.), and VAD (3, 10 and 30 mg/kg, i.p.) afforded significant gastroprotection (p<0,05) against absolute ethanol-induced gastric lesions. In the mechanistic studies, lupeol (30mg/kg) and VAD (10mg/kg) demonstrated an antioxidant action by preventing the ethanol-evoked depletion of non-protein sulfhydryls (NP-SHs), the involvement of nitric oxide (NO), prostaglandins (PGs), and the ATP-dependent potassium and calcium channels. Also observed were the participation of 2-adrenoceptors but not the opioid receptors in the gastroprotective effect of these substances. Lupeol (30 mg/kg) as well as DAV (10mg/kg) effectively reduced the total acidity (p<0,05) in the stomach without altering the gastric secretory volume in pylorus-ligatet rat. While normal intestinal transit was unalttered by lupeol (3, 10 e 30 mg/kg). VAD (3, 10 e 30 mg/kg) significantly (p<0,05) reduced by a mechanism that do not involve either opioid or adrenergic receptors. In addition, VAD (10 mg/kg) was also able to inhibit significantly (p<0, 05) the intestinal transit promoted by castor oil in mice. In open field test, lupeol (3, 10 e 30mg/kg) failed to demonstrate no significant change in locomotor activity of animals. However VAD (3, 10 e 30mg/kg) showed significant diminution (p<0,05) of locomotor activity in this test, but did not affect the motor coordination in rota-rod test. Mice treated with VAD (3,10 and 30mg/kg) demonstrated reduced latency and increase duration of sleeping time induced by pentobarbital sodium and showed enhanced immobility time in tail-suspension test. VAD at the doses 3, 10 and 30 mg/kg induced catalepsy in animals and at 10 mg/kg, it could effectively counteract the hypermotility induced by amphetamine (5mg/kg). These results suggest that both lupeol and VAD can affored gastroprotection against ethanol induced gastric injuri primarily through anantioxidant mechanism by restoring glutathione (NS-PH). The study futher indicate the possible involviment of NO, PGs, KATP channel activationaswell as membrane calcium. Besides the gastroprotection, DAV evidenced depressant effects in behavioral tests, possibly involving monoaminergic or adenosinergic systems which need to be clarifield in a future study.